2012
DOI: 10.1371/journal.pone.0031909
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Antibodies Against Coxiella burnetii and Risk of Spontaneous Abortion: A Nested Case-Control Study

Abstract: Background and AimsQ fever is a bacterial zoonosis caused by infection with Coxiella burnetii. It is well established that Q fever causes fetal loss in small ruminants. The suspicion has been raised that pregnant women may also experience adverse pregnancy outcome when the infection is acquired or reactivated during pregnancy. The purpose of this study was to assess the potential association between serologic markers of infection with C.burnetii and spontaneous abortion.MethodsA nested case-control study withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…In the present study, we used the indirect ELISA CHEKIT Q fever test to screen antibodies to C. burnetii among indigenous livestock in Saudi Arabia. The same test has been widely used for Q fever surveys in various species of ruminant farm animals and wild ungulates [16], as well as kangaroos [22] and even humans [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used the indirect ELISA CHEKIT Q fever test to screen antibodies to C. burnetii among indigenous livestock in Saudi Arabia. The same test has been widely used for Q fever surveys in various species of ruminant farm animals and wild ungulates [16], as well as kangaroos [22] and even humans [23].…”
Section: Discussionmentioning
confidence: 99%
“…The micro immunofluorescence antibody test (IFA) is regarded as the gold standard [20] because it is capable of determining both phase I and II antibodies simultaneously by the use of two different antigens in a single sample. We have previously demonstrated coherence between ELISA and IFA [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Villumsen et al established a national, very restrictive cutoff in order to obtain a high specificity and a high predictive value of a positive result [21]; this decision was based on the assumption that Q fever was sporadic in Denmark. However, particularly in rural populations of Denmark, Q fever is more widespread than previously considered [7,8] and one may now argue that the cutoff may be too conservative.…”
Section: Discussionmentioning
confidence: 99%
“…The current study is the first study investigating the relationship between the risk of abortion and Q fever seropositivity in our country. Similarly, in a study from Denmark, Nielsen et al [18], found no evidence of a higher prevalence of C.burnetii antibodies in serum samples from women who later miscarried and their study did not indicate a major association between Q fever infection and spontaneous abortion in humans.…”
Section: Discussionmentioning
confidence: 84%